Preparation and Characterization on Nano-Powder Al2O3-ZrO2 by Ultrasound Field Co-precipitation - Jiang, Fenghua (Asian Journal of Chemistry, 2013)
In this study, Al2(SO4)3·18H2O and ZrOCl2·8H2O were used as raw materials to synthesize Al2O3-ZrO2 nano-powder with an average diameter of 70 nm was prepared by co-precipitation method in the ultrasound field. The synthetic process and properties of nano-powder Al2O3-ZrO2 were studied by X-ray diffraction, differential thermal analysis, scanning electron microscopy and laser particle size analyzer. The results show that because of the activation ultrasonic radiation can not only make the precursor smaller and reduce it agglomeration but also slow down the speed of change to gel. Ultrasonic radiation can refine Al2O3-ZrO2 nano-powder effectively. The product was sphere-shaped particle with good dispersity.